Emancipation of The dominant technology space in Andrew Feinberg critical theory of technology - khashayar boromand; hassan husseini (حکمت و فلسفه, 2015)
Abstract The critical theory of technology is a title that Andrew Feinberg predicates to the results of his thoughts about technology. This title indicates explicitly that Feinberg is interested in critical thinking arising from the Frankfurt School. In the critical theory of technology, technology is considered neither evil nor accepted its development to its present form. On the one hand, Feinberg points to the risks of the dominant technology space and on the other hand, he believes that the technological development isn't dangerous completely. In the critical theory of technology, the technologies are analyzed in both functional and external realization. According to this analysis, undesirable consequences of modern technology will be obvious in its current form. Feinberg does not suffice to disply such undesirable consequences and he considers releasing from the dominant technology based on democratic values. In his view, the liberation strategy is trying to realize another form of modernity that is formed based on a wider range of values. In this article, firstly we will explain the main elements of critical theory of technology and then we will point to emancipatory aspect of Feinberg approach for going out of the dominant technology space and realizing of alternative modernity as his ideal. Finally, there are mentions about some of the problems with this approach and the relationship between the critical theory of technology and the share of national culture in technological design.